Characterisation of low earth orbit satellite channels - Phua, Chee Teck (2008)
Satellite propagation studies had been widely covered in various literature. Researchers had derived numerous models to describe various aspects of the channel. Many such works were done for the microwave frequencies using geostationary satellites or helicopters. However, this project utilised signals collected from a Low Earth Orbiting (LEO) amateur satellite (UoSAT-5), operating in the UHF band, for channel characterisation.